Peripheral Arterial Disease A Practical Approach - Sareen, Nishtha; Ojha, Abhishek (IntechOpen, 2018)
"Peripheral Arterial Disease - A Practical Approach" is an honest effort to provide a clinically relevant approach to the management plan in patients presenting with peripheral vascular symptoms. We have summarized the most pertinent practical aspects of peripheral vascular disease, their clinical implications, diagnostic testing, therapeutic interventions and innovations. We hope this book serves as a reference for basic and advanced peripheral vascular care.